Plan de negocio. Creación del departamento de comercio internacional para la empresa PaNi Pets, para la comercialización de ropa para mascotas a Vancouver Canadá (2019)
The company PaNi Pets was founded in 2016 in the city of Bogotá, Colombia, responsible for the manufacture of pet clothes like, waterproof vests, wool coat and cotton coats with "Adidog" print; wants to open its International Trade Department, to expand its operations and enter in that way, to the Canadian pet market. For this purpose, a very clear and detailed market study will be required, in order to determine the potential of this market in the city of Vancouver. The analysis of the market study will dictate the strategies and plans that the company must follow, in order to successfully enter the Canadian market, which is very competitive. The company realizing that, makes the decision to make a commercial alliance with a distributor in the city of Vancouver, which will allow a strong and secure income.